二元連立方程式
p = ax + by
q = cx + dy
普通の代入
をx,yについて解くと
第一式をc、第二式をa倍して
cp = acx + cby
aq = acx + ady
ひいて
(cb - ad)y = cp - aq
y = \frac{cp - aq}{cb - ad}
第一式に代入
p = a x + b(\frac{cp - aq}{cb - ad})
a x = p - b(\frac{cp - aq}{cb - ad})
x =\frac{1}{a} \{ p - b(\frac{cp - aq}{cb - ad}) \}
=\frac{1}{a} \frac{ p(cb - ad) - b({cp - aq}) }{cb - ad }
=\frac{1}{a} \frac{ - p(ad) + b({ aq}) }{cb - ad }
=\frac{1}{a} \frac{ {abq}- adp }{cb - ad }
=\frac{ bq- dp }{cb - ad }
x= \frac{ dp - bq }{ad - bc }
y = \frac{aq - cp}{ad - bc}
行列での表記
A ^ { - 1 } = \frac { 1 } { a d - b c } \left( \begin{array} { c c } { d } & { - b } \\ { - c } & { a } \end{array} \right)